2011
DOI: 10.48102/pi.v19i2.225
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar subjetivo y satisfacción con la vida de familia en adolescentes mexicanos de bachillerato

Abstract: El objetivo del presente estudio fue examinar la relación entre el Bienestar Subjetivo y la Satisfacción Familiar en adolescentes, desde la perspectiva de la Psicología Positiva. La muestra (N = 580) se compuso de estudiantes de bachillerato con edades entre 15 y 19 años, quienes respondieron la Escala Multidimensional para la Medición del Bienestar Subjetivo de Anguas-Plata y Reyes-Lagunes (Anguas, 2000, 2001), la Escala de Satisfacción con Aspectos de la Vida (basada en Diener, Emmons, Larsen & Griffin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
5
Order By: Relevance
“…Moreover, studies found positive correlations between family satisfaction ( n = 47) and happiness [ 142 , 143 , 144 ], identifying satisfaction with family life as the strongest predictor of overall life satisfaction, from childhood to adolescence [ 3 , 29 , 35 , 42 , 145 , 146 ]. In particular, family satisfaction correlated positively with both the affective component (i.e., positive affect and positive emotions) and the cognitive component (i.e., life satisfaction) of happiness [ 36 , 37 , 71 , 147 , 148 , 149 , 150 ]. Furthermore, family life satisfaction was positively associated with children’s positive affect [ 148 , 151 , 152 , 153 ] and happiness [ 38 , 126 ], from the perspectives of both children [ 1 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ] and parents [ 27 , 73 , 168 , 169 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies found positive correlations between family satisfaction ( n = 47) and happiness [ 142 , 143 , 144 ], identifying satisfaction with family life as the strongest predictor of overall life satisfaction, from childhood to adolescence [ 3 , 29 , 35 , 42 , 145 , 146 ]. In particular, family satisfaction correlated positively with both the affective component (i.e., positive affect and positive emotions) and the cognitive component (i.e., life satisfaction) of happiness [ 36 , 37 , 71 , 147 , 148 , 149 , 150 ]. Furthermore, family life satisfaction was positively associated with children’s positive affect [ 148 , 151 , 152 , 153 ] and happiness [ 38 , 126 ], from the perspectives of both children [ 1 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ] and parents [ 27 , 73 , 168 , 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…As conflict tends to generate negative emotions, high-conflict families have been found to be associated with lower levels of happiness and life satisfaction [ 33 ]. On the other hand, family satisfaction, defined as the extent to which individuals feel satisfied with the level of perceived support from family members [ 34 ], has been shown to be associated with increased happiness and overall life satisfaction in children and adolescents [ 35 , 36 , 37 , 38 ]. Other studies have confirmed that a dysfunctional family relationship (e.g., low-income, family coherence, family conflict) is a risk factor for children’s and adolescents’ happiness [ 32 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies that corroborate the significance of such differences in favor of women ( Arocena et al, 2005 ; Lalive et al, 2014 ; Al-Attiyah and Nasser, 2016 ; Rojas-Valverde and Fallas-Campos, 2017 ; Cañero et al, 2019 ). Some research using even smaller groups found differences in life satisfaction in favor of men ( Pavot et al, 1991 ; Smith et al, 1999 ; Bernal et al, 2011 ; Lukaschek et al, 2017 ; Tomyn and Weinberg, 2018 ). Recent research has shown greater interest in studying this variable because of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados sugieren que ambas formas de bienestar re(ejan una estructura de bienestar global con una alta correlación r= .96. Así mismo, se cuenta con estudios que asocian metas personales (propósito en la vida) y satisfacción vital o BS (Álvarez & Montoya, 2020;Castro & Díaz, 2002; con satisfacción vital familiar (Cardoza et al, 2019;Luna et al, 2011;Vergaray & Benavides, 2020), funcionamiento positivo, autorrealización y BP (Delgado & Tejeda, 2020;González-Fuentes & Andrade, 2016;Gutiérrez-Carmona et al, 2020). En esta misma línea, la teoría de la autodeterminación (TAD, Self-Determination Theory) de Ryan y Deci (2000), se encuentra orientada hacia la motivación personal.…”
Section: Introductionunclassified